Instructors’ Experience with Using ICT in Facilitating Student teachers Learning in selected Teachers colleges in Morogoro, Tanzania - Machumu, Haruni; Josephaty, John; Zhu, Chang; Anania, Ahadi (Journal of Policy and Leadership, 2022)
The integration of information and communication technology (ICT) into present teachers' colleges is predicated on instructors' experience and skills, as it facilitates the design of appropriate educational environments. However, instructors' experience and teaching skills with ICT in organizing and managing the ICT-based teaching and learning process are insufficient. This study investigates instructors’ teaching skills and experiences in the use of ICT in facilitating student-teacher learning in Tanzanian teachers' colleges. The study was conducted in two teachers' colleges in Morogoro using 40 respondents. The study employed a mixed methods research design to collect data through questionnaires, interview guides and documentary review. Simple random sampling was used to select 36 instructors, and purposive sampling was used to select college principals and ICT specialists. Quantitative data are presented in tables showing frequency, percentage, mean and standard deviation, while data from the interview are presented in quotation marks, for explicit interpretation. Qualitative data were thematically analysed, while quantitative data were descriptively analysed. The findings reveal that instructors possessed several ICT teaching skills and experiences used in facilitating student-teacher learning. These comprise the use of internetbased digital content, resources, word processing and PowerPoint presentation skills. Furthermore, web-based video conferencing was found as scarcely used among instructors due to their lack of skills. It is recommended that the government and other education stakeholders should aim to provide in–house training to cement essential current ICT skills for instructors, to better facilitate student-teacher learning and better prepare them for future teaching careers.